Biased Policy Professionals - Banuri, Sheheryar; Dercon, Stefan; Gauri, Varun (The World Bank Economic Review, 2019)
Although the decisions of policy professionals are often more consequential than those of individuals in their private capacity, there is a dearth of studies on the biases of policy professionals: those who prepare and implement policy on behalf of elected politicians. Experiments conducted on a novel subject pool of development policy professionals (public servants of the World Bank and the Department for International Development in the UK) show that policy professionals are indeed subject to decision-making traps, including the effects of framing outcomes as losses or gains, and, most strikingly, confirmation bias driven by ideological predisposition, despite having an explicit mission to promote evidence-informed and impartial decision making. These findings should worry policy professionals and their principals in governments and large organizations, as well as citizens themselves. A further experiment, in which policy professionals engage in discussion, shows that deliberation may be able to mitigate the effects of some of these biases.
Keywords: bias

EvalC3 - Davies, Rick (2019)
Tools for developing, exploring and evaluating predictive models of expected outcomes

Failing Forward: How CARE is Focusing on What Goes Wrong to Improve Impact - Janoch, Emily (CARE, 2019)
CARE's Failing Forward initiative is sparking opportunities to showcase the ideas that don't work so we can spend more time implementing the ones that do. It's changing the conversation inside the organization, and leading to changes in the way we design and implement programs.

How We Model Matters: A Manifesto for the Next Generation of Program Theorizing - Whynot, Jane; Lemire, Sebastian; Montague, Steve (Canadian Journal of Program Evaluation, 2019)
In this concluding article, grounded on the exemplary contributions contained in the preceding pages, the guest editors scale the proverbial soapbox and present a manifesto to guide the pursuit and advancement of the next generation of program theorizing. Formulating ten declarations for program theory development and examination, the modest hope of the authors is to motivate and inspire reflective evaluation practitioners to broaden their views, approaches, and techniques for future program theorizing.

Monitoring and Result Measurement for Adaptive Programming - How to Use Data to Manage a MSD Program: Lessons from PRISMA - Khan, Khaled; Seely, Kevin; Ridwan, Mustika; Mulya, Bodhiya (PRISMA, 2019)
Using monitoring data to improve interventions is harder than it seems. Decision-makers are often busy implementing activities, unclear about their roles in data collection and analysis, and uncertain what data matters most or when. PRISMA, an AUD77 million agricultural Market Systems Development (MSD) programme funded by DFAT Australia, has encountered these challenges. With the programme completing its first five year phase, this case study shares ten key lessons divided into three sections: shaping the culture, developing systems, and top management decisions. These lessons aim to help program, sector and intervention managers make better use of monitoring data to improve interventions.

Peacebuilding design, monitoring, and evaluation: A Training Package for participants and trainers at intermediate to advanced levels - Ernstorfer, Anita; Barnard-Webster, Kiely (Carnegie Corporation, 2019)
This training package includes 7 Training Modules and a set of Annexes (Annexes A-O). The Training Modules build on each other and should ideally be used in a sequenced way in a training setting. However, for groups with specific training needs around particular areas, modules can also be used individually, but need to be tailored by the trainers and facilitators to meet the needs of specific audiences. The annexes provide worksheets and hand-outs that can be used as resources during the training for specific modules and exercises.

Supporting users with the OutNav approash - Matter of Focus (2019)
This report has been generated in OutNav, using the theory-based approach to evaluation pioneered by Matter of Focus. Example of a report from the tool, explaining OutNav approach

The M&E (Monitoring & Evaluation) Universe - INTRAC (INTRAC, 2019)
The M&E Universe is a free, online resource developed by INTRAC to support development practitioners involved in monitoring and evaluation (M&E). It consists of a series of short papers (2-6 pages) on different subjects related to M&E. To begin exploring the Universe right away, use the button below. To find out more, read on.

The Rapid Evaluation, Action, and Learning (REAL) Approach: A toolkit to measure and refine changes and interventions in health campaigns - PATH (PATH, 2019)
Evaluative Tools for Improving Campaign Effectiveness Public health campaigns aim to control disease or deliver essential health services and products through time-limited and periodic channels. Many countries use campaigns to augment or replace routine service delivery, to target certain populations, or to accelerate progress towards coverage targets. The Root Cause Analysis and Rapid Evaluation, Action, and Learning toolkits present a systematic but flexible approach to identifying the root causes of campaign bottlenecks and then designing, testing, and refining solutions to optimize potential impact. These toolkits respond to a growing need for “fit-for-purpose” rapid-testing, adaptive learning approaches to evaluation and the need for a culture shift toward iterative adaptation and improvement that integrates measurement and evidence-informed decision-making into daily practice. The comprehensive package of toolkits, in addition to the individual Root Cause Analysis toolkit and Rapid Evaluation, Action, and Learning toolkit are available below.

Thinking and Working Politically in Economic Development Programmes – Some Sprints and Stumbles from a DFID Programme in Kyrgyzstan - Koleros, Andrew; Rinnert, David (From Poverty to Power, 2019)
A DFID programme in Kyrgyzstan offers useful insights into how the Thinking and Working Politically approach can escape from its governance ghetto
Keywords: Case Study